Advanced glycation end-products accelerate telomere attrition and increase pro-inflammatory mediators in human WIL2-NS cells. (22nd April 2020) - Deo, Permal; Dhillon, Varinderpal S; Lim, Wai Mun; Jaunay, Emma L; Donnellan, Leigh; Peake, Brock; McCullough, Caitlin; Fenech, Michael
Abstract: This study investigated the effect of dietary sugars and advanced glycation end-products (AGE) on telomere dynamics in WIL2-NS cells. Dietary sugars [glucose (Glu) and fructose (Fru); 0.1 M each] were incubated with bovine serum albumin (BSA) (10 mg/ml) at 60 ± 1°C for 6 weeks to generate AGE-BSA. Liquid chromatography-mass spectrometry (LC-MS/MS) analysis showed total AGE levels as 87.74 ± 4.46 nmol/mg and 84.94 ± 4.28 nmol/mg respectively in Glu-BSA and Fru-BSA model. Cell treatment studies using WIL2-NS cells were based on either glucose, fructose (each 2.5–40 mM) or AGE-BSA (200–600 µg/ml) in a dose-dependent manner for 9 days. Telomere length (TL) was measured using qPCR. Nitric oxide (NO) production and tumour necrosis factor-α (TNF-α) levels were measured in WIL2-NS culture medium. An increasing trend for TNF-α and NO production was observed with higher concentration of glucose ( R 2 = 0.358; P = 0.019; R 2 = 0.307; P = 0.027) and fructose ( R 2 = 0.669; P = 0.001; R 2 = 0.339; P = 0.006). A decreasing trend for TL ( R 2 = 0.828; P = 0.000), and an increasing trend for NO production ( R 2 = 0.352; P = 0.031) were observed with increasing Glu-BSA concentrations. Fru-BSA treatment did not show significant trend on TL ( R 2 = 0.135; P = 0.352) with increasing concentration, however, a significant reduction was observed at 600 µg/ml ( P < 0.01) when compared to BSA treatment. No trends for TNF-α levels and a decreasing trend on NO production ( R 2 = 0.5201; P = 0.019) was observed with increasing Fru-BSA treatment. In conclusion, this study demonstrates a potential relationship between dietary sugars, AGEs and telomere attrition. AGEs may also exert telomere shortening through the production of pro-inflammatory metabolites, which ultimately increase the risk of diabetes complications and age-related disease throughout lifespan.